TREATMENT OF A CHRONIC OBSTRUCTIVE PULMONARY DISEASE CASE WITH REGENTIME® PROCEDURE - Rita T. Boulos; Lea I. Nemer; Vanessa J. Mansour; Nassim H. Abi Chahine, (EPRA International Journal of Research and Development (IJRD), 2022)
Chronic Obstructive Pulmonary Disease (COPD) is a common disease associated with high morbidity and mortality rates. It is characterized by airway and parenchymal inflammation leading to airway narrowing, decreased lung recoil, and eventual airflow limitation. Despite the advance in therapeutic approaches, no curative clinical treatment for COPD exists. We present the case of a 74-year-old gentleman diagnosed with COPD who underwent stem cell therapy with the Regentime® Procedure. This technique uses Autologous Bone Marrow -Mononuclear Stem Cells (BM-MSCs) which are partially differentiated and specifically redirected to the desired organ. Clinical follow-up 5 years after transplantation showed a decrease in major symptoms, including dyspnea, cough, fatigue, and decreased oxygen requirement. However, regression was registered during the past 2 years during which the patient’s oxygen requirement increased for optimal oxygen saturation. The results obtained support stem cell-based therapy as a promising therapeutic option for patients suffering from COPD.